Phytoplankton responses to atmospheric metal deposition in the coastal and open-ocean Sargasso Sea - Mackey, Katherine R.; Buck, Kristen N.; Casey, John R.; Cid, Abigail; Lomas, Michael W.; Sohrin, Yoshiki; Paytan, Adina (Frontiers in Microbiology, 2012)
This study investigated the impact of atmospheric metal deposition on natural phytoplankton communities at open-ocean and coastal sites in the Sargasso Sea during the spring bloom. Locally collected aerosols with different metal contents were added to natural phytoplankton assemblages from each site, and changes in nitrate, dissolved metal concentration, and phytoplankton abundance and carbon content were monitored. Addition of aerosol doubled the concentrations of cadmium, cobalt, copper, iron, manganese and nickel in the incubation water. Over the three-day experiments, greater drawdown of dissolved metals occurred in the open ocean water, whereas little metal drawdown occurred in the coastal water. Two populations of picoeukaryotic algae and Synechococcus grew in response to aerosol additions in both experiments. Particulate organic carbon (POC) increased and was most sensitive to changes in picoeukaryote abundance. Phytoplankton community composition differed depending on the chemistry of the aerosol added. Enrichment with aerosol that had higher metal content led to a 10-fold increase in Synechococcus abundance in the oceanic experiment but not in the coastal experiment. Enrichment of aerosol-derived cobalt (Co), manganese, and nickel were particularly enhanced in the oceanic experiment, suggesting the Synechococcus population may have been fertilized by these aerosol metals. Copper (Cu)-binding ligand concentrations were in excess of dissolved Cu in both experiments, and increased with aerosol additions. Bioavailable free hydrated Cu2+ concentrations were below toxicity thresholds throughout both experiments. These experiments show (1) atmospheric deposition contributes biologically important metals to seawater, (2) these metals are consumed over time scales commensurate with cell growth, and (3) growth responses can differ between distinct Synechococcus or eukaryotic algal populations despite relatively close geographic proximity and taxonomic similarity.